Asuhan Keperawatan Anak Pada Pasien Dengan Kejang Demam Di Ruangan Marwa Rumah Sakit Aisyiyah Pariaman Tahun 2026 - Dwi Mustika Putri Ritonga; Reska Handayani; Prima Yoselina; Yessy Aprihatin (CV. ITTC INDONESIA, 2026)
Febrile seizures are episodes of convulsions that occur due to an increase in body temperature above 38°C without any associated intracranial disorders, and they most commonly affect children aged 6 months to 5 years. This study aims to describe the implementation of nursing care for children with febrile seizures. The method used in this study is a case study with a nursing process approach, which includes assessment, nursing diagnosis, intervention planning, implementation, and evaluation stages. The subject of the study was a child diagnosed with febrile seizures who was treated at Aisyiyah Hospital Pariaman from February 13 to 16, 2026. Based on the study results, the identified nursing problems were hyperthermia, risk of injury, and sleep pattern disturbance. The nursing interventions implemented included hyperthermia management, environmental safety management, and sleep support. After four days of care, the patient’s condition showed improvement, indicated by the return of body temperature to normal, no recurrence of seizures, improved sleep patterns, and the patient appearing calmer. In conclusion, the systematic and continuous implementation of nursing care has proven to be effective in addressing nursing problems in children with febrile seizures and in improving the patient’s health condition and quality of rest.